Strengthening anticipatory action with the Early Warning, Early Action and Early Finance (AWARE) Platform: a Gender Equality and Social Inclusion (GESI) lens for inclusive resilience - Ariyabandu, Madhavi Malalgoda; Amarnath, Giriraj; Aheeyar, Mohamed M. M.; Alahacoon, Niranga; Kotuwegoda, S. (International Water Management Institute, 2025)
Anticipatory action (AA) is an emerging approach in disaster management that aims to reduce the humanitarian impacts of potential disasters through proactive and integrated measures. The AWARE platform, a component of the CGIAR initiative on Climate Resilience ('ClimBeR') and CGIAR Climate Action Program, facilitates the coordination of AA by connecting risk and vulnerability information, early warning systems, and proactive measures for mitigating disaster impacts. However, the effectiveness and equity of AA depend on reaching the most vulnerable groups in at-risk communities, which requires understanding and addressing their unique vulnerabilities and capacities. The integration of gender and social inclusion (GESI) in AA planning and execution is critical for maximizing the effectiveness and equity of interventions. The GESI strategy consists of two main elements: (i) inclusive participation and equitable access, and (ii) addressing vulnerabilities while strengthening the capacities of diverse community groups to manage disaster risk. Comprehensive social and gender analysis constitutes the basis for the strategic and effective planning and implementation of AA. This analysis informs the development of criteria, facilitates engagement with diverse community groups, and aids in the identification of suitable interventions. The AWARE platform supports risk governance, a key requisite for GESI, and empowers vulnerable groups by engaging in risk assessment, planning, and execution. Pre-arranging finances informed by context-specific social and gender analysis supports resource mobilization and allocation for inclusive programming and delivery. The guiding principles assigned to each building block of AA strives to navigate challenges and seize opportunities for GESI integration. By embedding the principles of inclusion and equity, the AWARE platform aims to ensure AA interventions are transformative and adhere to the principle of ‘Leave No One Behind.’